Mechanochemical post-synthesis of metal–organic framework-based pre-electrocatalysts with surface Fe O Ni/Co bonding for highly efficient oxygen evolution - Zhang, Wang (2023)
Rational surface engineering of metal–organic frameworks (MOFs) provide potential opportunities to address the sluggish kinetics of oxygen evolution reaction (OER). However, the development of MOF-based materials with low overpotentials remains a great challenge. Herein, a post-synthesis strategy to prepare highly efficient MOF-based pre-electrocatalysts via all-solid-phase mechanochemistry is demonstrated. The surface of a Fe-based MOF (MIL-53) can be reconstructed and anchored with atomically dispersed Ni/Co sites. As expected, the optimized M-NiA-CoN exhibits a very low overpotential of 180 mV at 10 mA cm−2 and a small Tafel slope of 41 mV dec−1 in 1 m KOH electrolyte. The superior electrocatalytic OER activity is mainly due to the formation of surface Fe O Ni/Co bonding. Furthermore, density functional theory calculations reveal that the transformation from *OH to *O is the rate-determining step and the electrocatalytic OER activity trend at different metal sites is Co > Ni≈Fe.